Towards Discursive Economics: Methodology and History of Economics Revised - Владимир Максович Ефимов (Journal of Economic Sociology, 2011)
One had to know the rules governing diverse actors’ behavior on the USA housing market to recognize the enlarging bubble and foresee an inevitable crash. Apart from the market actors, the experts being in direct contacts with these actors (for example, conducting in-depth interviews) could be aware of these rules. Generally speaking, social and economic regularities are generated by the fact that people behave according to the socially constructed rules which are explained, argued and learnt through telling stories. It means that we should analyze these stories for revealing the social and economic regularities. As far as the modern economics is not interested in studying economic actors’ discourses, it loses a capacity to understand and foresee important economic phenomena. Discourse analysis does not imply a departure from the strict scientific standards with their origins in natural sciences; it rather comes closer to them because all social interactions are mediated by language. The paper proposes an alternative to a variety of forms developed by institutional economics as well as most recent perspectives of economic theory including behavioral and experimental economics. The first part of the paper published in the current issue of the journal (May 2011) describes discursive methodology and its recent applications to the analysis of economic phenomena. The second part of the paper will be published in the next journal issue (September 2011). It is devoted to a discursive analysis of history and the present status of economics. It revises the results of «Methodenstreit» and discusses conditions which could give a way to the radical reform of mainstream economics.  институциональное знание